Wild fruit collection and its impact on household food security in the Luapula Province, Zambia - Ronja Seegers (Transformationsprozesse in Stadt und Land: Erkenntnisse, Strategien und Zukunftsperspektiven, 2024)
In many sub-Saharan African countries, wild fruits offer great potential to serve as a nutritional complement and safety net in times of food shortages. However, their true contribution to food security is still insufficiently investigated. This study, therefore, examines the impact of wild fruits on the food security of 215 households in Northern Zambia. Data were collected through focus group discussions and a census. The Food Consumption Score (FCS) and reduced Coping Strategy Index (rCSI) were calculated as food security indicators. Results of multiple linear regression analysis reveal no relationship between wild fruit collection and the rCSI. However, households with a lower FCS rely more on wild fruit collection to diversify their diets and can significantly improve their food security the more fruits they collect. Thus, households do not consider wild fruit collection as a coping strategy in times of food scarcity but rather use wild fruits as nutritional complements to a regular diet. – – In vielen afrikanischen Ländern südlich der Sahara bieten Wildfrüchte großes Potenzial, als Nahrungsergänzung und Sicherheitsnetz in Zeiten von Nahrungsmittelknappheit zu dienen. Ihr tatsächlicher Beitrag zur Ernährungssicherung ist jedoch noch unzureichend erforscht. Diese Studie untersucht daher die Auswirkungen von Wildfrüchten auf die Ernährungssicherung von 215 Haushalten im Norden Sambias. Die Daten wurden durch Fokusgruppendiskussionen und eine Volkszählung erhoben. Der Food Consumption Score (FCS) und der reduced Coping Strategy Index (rCSI) wurden als Indikatoren für die Ernährungssicherung berechnet. Die Ergebnisse der multiplen linearen Regressionsanalyse zeigen keinen Zusammenhang zwischen dem Sammeln von Wildfrüchten und dem rCSI. Haushalte mit einem niedrigeren FCS sind jedoch stärker auf das Sammeln von Wildfrüchten angewiesen, um ihre Ernährung zu diversifizieren, und können ihre Ernährungssicherung deutlich verbessern, je mehr Früchte sie sammeln. Die Haushalte betrachten das Sammeln von Wildfrüchten also nicht als Bewältigungsstrategie in Zeiten der Nahrungsmittelknappheit, sondern nutzen diese vielmehr als Ergänzung zur normalen Ernährung.
urn:nbn:de:0156-1171121; hdl:10419/285312; https://econpapers.repec.org/RePEc:zbw:arlfob:285312
Keywords: 710; Wild Fruits; Food Security; Food Consumption Score; Reduced Coping Strategy Index; Zambia; Wildfrüchte; Ernährungssicherung; Sambia